EDUCATION IN RURAL AREAS IN THE SELECTED EU COUNTRIES ON THE EXAMPLE OF EDUCATIONAL FARMS - Alexandru SIN; Czesław NOWAK; Małgorzata BOGUSZ; Elżbieta KMITA-DZIASEK; Magdalena KOWALSKA (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development)
Education in rural areas, more and more frequently, takes place in agricultural holdings which address their educational offer, in particular, to specific groups of children and youth. The aim of the paper was to characterize such holdings in the selected EU countries. The characterization was based on the results of research obtained from two sources, firstly, the international FARMLAND project, secondly, the original study conducted by the authors in Poland and Romania. The research results clearly point to the development of educational activities in agricultural holdings, with the use of natural and cultural resources of the given areas.